Respiratory obstruction due to richards type 4 fracture - Pires, Willian Ricardo [UNESP]; Santos, Gabriel Mulinari [UNESP]; De CarvalhoReis, Erik Neiva Ribeiro [UNESP]; De Oliva, André Hergesel [UNESP]; Jacob, Ricardo Garcia Mureb [UNESP]; Faverani, Leonardo Perez [UNESP]; Souza, Francisley Ávila [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP] (Wolters Kluwer, 2018)
Facial fractures can be potentially fatal in polytraumatized patients due to retropositioning tissues to upper airway obstruction. In the first AIDS, this situation can be reversed using a tracheostomy procedure to break out the airways. However, fractures leading to airway obstruction are rare and according to Richards Classification can be classified into 5 types. The purpose of this article is to report a clinical patient with a bilateral condylar and mandibular symphysis fractures that resulted in airway obstruction and severe mandibular rear projection.
Keywords: Airway obstruction; mandible; mandibular condyle; mandibular fractures; mandibular injuries; tracheostomy